2020
DOI: 10.3389/fmicb.2020.00597
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus murinus Improved the Bioavailability of Orally Administered Glycyrrhizic Acid in Rats

Abstract: Intestinal microbiota has been extensively studied in the context of host health benefit, and it has recently become clear that the gut microbiota influences drug pharmacokinetics and correspondingly efficacy. Intestinal microbiota dysbiosis is closely related with liver cirrhosis, especially the depletion of Lactobacillus. Therefore, the bioavailability of orally administered glycyrrhizic acid (GL) was speculated to be influenced under a pathological state. In the present study, L. murinus was isolated and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…ACAG protected against 2,4,6-trinitrobenzene sulfonic acid-induced colitis through anti-inflammatory and antioxidant effects (Xu B.-L. et al, 2015). However, the constituents in ACAG, such as puerarin (Li et al, 2014a), daidzin (Murota et al, 2002), baicalin (Wu et al, 2014), berberine (Liu et al, 2016), and glycyrrhizic acid (Yuan et al, 2020), have poor solubility, permeability, or metabolic stability; thus, improving their oral bioavailability is challenging.…”
Section: Discussion and Perspectives Effective Constituentsmentioning
confidence: 99%
“…ACAG protected against 2,4,6-trinitrobenzene sulfonic acid-induced colitis through anti-inflammatory and antioxidant effects (Xu B.-L. et al, 2015). However, the constituents in ACAG, such as puerarin (Li et al, 2014a), daidzin (Murota et al, 2002), baicalin (Wu et al, 2014), berberine (Liu et al, 2016), and glycyrrhizic acid (Yuan et al, 2020), have poor solubility, permeability, or metabolic stability; thus, improving their oral bioavailability is challenging.…”
Section: Discussion and Perspectives Effective Constituentsmentioning
confidence: 99%
“…Yuan et al. 42 reported that Lactobacillus murinus could enhance the bioavailability of oral administered glycyrrhizic acid (GL) by significantly downregulating the efflux transporter gene expression level of multidrug resistance gene 1 ( MDR1 ) and multidrug resistance protein 2 (MRP2) in vitro . They also found that the supplements of L. murinus could prominently increase the bioavailability of GL in rats with liver cirrhosis, indicating a potential strategy for enhancing the efficacy of liver protective drugs in the clinical treatment.…”
Section: The Alteration In the Drug Transportmentioning
confidence: 99%
“…In addition, it may also offer us many innovative ideas of the drug delivery system design, especially the design of colon-targeted drug delivery systems. Herein, we provide a review to document the recent discoveries of the possible interactions of the gut microbiota, host and oral drugs by which the bioavailability may be affected (as shown in Table 1 24 , 25 , 26 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ) and make suggestions for further research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The environment created by tissue culture could mimic the nasal and oral mucosa to a great extent. For instance, oral glycyrrhizic acid is converted to glycyrrhetic acid (more toxic) by intestinal commensal bacteria, where glycyrrhizic acid itself becomes indetectable in the plasma ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%